A new population of the hooded antpitta (Grallaricula cucullata: Grallaridae) for the Colombian Central Andes (2015)
We report a new population of the Hooded Anpitta (Grallariculla cucullata) in the Central Andes of Colombia, a threatened bird species inhabiting montane cloud forests in Colombian and Venezuelan Andes. We present capture-rate data, which suggest the occurrence of a resident with the highest population size reported for this bird species.